The efficacy of exergames-incorporated physical education lessons in influencing drivers of physical activityn : a comparison of children and pre-adolescents - Lwin, May Oo (2013)
Objective: This study examines the efficacy of incorporating exergaming into physical education (PE) lessons among children and pre-adolescents in influencing the social cognitive factors and behaviors of physical activity (PA), based on the theory of planned behavior (TPB).